Amanat Lakon Pusaka Gedhong Semara Dhenok pada Wayang Topeng Malang - Robby Hidajat (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2006)
Abstract Malang Mask Puppet show in Kedungmonggo has uniqueness in the development of Panji act. One of the acts performed prior to the evening of village-cleaning ceremony is Pusaka Gedhong Semara Dhenok. The massage of the act basically is associated with the fertility myth and the concept of duality. In addition to this massage the act tries to demonstrate the local wisdom of the people in that village. The act Pusaka Gedhong Semara Dhenok displays a complexity on the rhetoric of the community, which comprises of the recognition on sociocultural aspect and believe including the understanding of the society toward the character’s typology ang the characteristic of human being in general. Key words: Mask Puppet, structure, village-cleaning ceremony, sociocultural